Framework for supporting JavaScript-Based Mobile Agents - Villafuerte, Carlos Alfredo Silva (2018)
The evolution of technology in interconnection solutions, such as networks or the Internet, and the emergence both of wireless sensors networks and distributed systems allowed many communication architectures to appear, being the Client-server architecture the most common. Here, we present a dissertation work about the mobile agents computing paradigm. A middleware and a mobile agent framework have been developed using the JavaScript language that allows the development, execution and the ability to move JavaScript mobile agents through the local network and Internet using Node.js for desktop operating systems and React Native for mobile operating systems, such as Android and iOS. This initiative arose as a way of dealing with problems raised by the considerable amount of existing Java based mobile agents platforms, which force the installation of the Java Virtual Machine on the devices, making complicated its execution in operating systems like macOS, iOS and others operating systems not compatible with Java.